KINERJA KEUANGAN, INFLASI DAN RETURN SAHAM: STUDI PADA PERUSAHAAN PUBLIK SUB SEKTOR TRANSPORTASI PERIODE 2010-2017 - PUTRI ARLYISTA, EUNIKE; SISTA PARAMITA, R.A. (Jurnal Ilmu Manajemen (JIM), 2019)
Capital markets have an important contribution to the companies in fulfilling funds and distribution funds through investment. Many companies trade financial instrument such as shares. Investors who are interested to buying company shares, will get a return. This study aims to analyze the factors that influence the stock return of the transportation sub sector. Sector transportation was choosen due to the gap of phenomenon between the transportation users according to BPS, which tends to increase, but the return of the transportation sector companies fluctuates. The number of samples in this study were 11 companies with 8 years of observation so that as a whole amounted to 88 datas. The variable were observed in this study are financial ratio, inflation and return being analized using multiple linear regression analysis. The results of the F test in this study indicate that simultaneously financial performance and inflation affect stock returns. Whereas, the results of the t test show that the variables CR and EPS have no effect on stock returns. The variable DER has significant positive effect on stock returns, the variable TATO and inflation has a significant negative effect on stock returns. Based on the results of this study, the implication is that investors are expected to pay more attention value of DER, TATO and inflation in making investment decisions. Keywords: financial performance; inflation; stock return